4 Iron deficiency in heart failure patients in england: insights from analysis of hospital episode statistics. (5th June 2017) - M Beattie, James; Khatib, Rani; Phillips, Ceri; Williams, Simon G
Abstract : Introduction: Iron deficiency (ID) has been shown to be present in about 50% of patients with heart failure (HF). Associated with a poor quality of life, impaired effort tolerance, and increased mortality, ID responds to appropriately provided iron therapy. In those admitted with HF, screening for ID is inconsistent, and the impact of this condition is uncertain. Methods: For the period April 2013 to March 2016 (2013–16), Hospital Episode Statistics (HES) data from all NHS hospitals in England were evaluated for spells in which HF was coded as the primary diagnosis. This was based on the International Statistical Classification of Diseases and Related Health Problems (ICD-10) codes: I11.0 (hypertensive heart disease with [congestive] heart failure; I25.5 (ischaemic cardiomyopathy); I42.0 (dilated cardiomyopathy); I42.9 (cardiomyopathy, unspecified); I50.0 (congestive heart failure); I50.1 (left ventricular failure); and I50.9 (heart failure, unspecified). These records were then categorised according to those with or without a secondary diagnosis of ID or iron deficiency anaemia (IDA), based on ICD-10 codes E611 (latent ID), D500 (IDA secondary to blood loss [chronic]), D508 (other IDA), and D509 (IDA unspecified). Results: In 2013–16, there were 2 02 444 hospital spells in England attributed to a primary diagnosis of HF. Of these, 28 727 spells (14.2%) had a secondary diagnosis of ID/IDA, and 1 73 717 (85.8%) did not. Spells with a secondary diagnosis of IDA/ID were more likely to be encountered in females (p<0.0001) and older patients (p<0.0001); were more likely to be unplanned (95.9% vs 86.4% – difference 9.5%: 95% CIs: 9.2%, 8%); had a longer mean length of stay (16.5 vs 13.1 days – difference 3.4 days: 95% CIs: 3.2, 3.6); and had a higher readmission rate within 30 days under the same ICD-10 code (14.2% vs 12.1% – difference 2.1%: 95%CIs: 1.8%, 2.6%). The total cost associated with all hospital admissions with a primary diagnosis of HF was £553.3 million, equivalent to £2733 per spell. HF hospital spells with a secondary diagnosis of ID/IDA were significantly more expensive than those without (cost difference: £138 per spell [95% confidence interval CI: £98, £178]). Unplanned spells with a secondary diagnosis of ID/IDA were even more expensive compared to those without ID/IDA (cost difference: £217 [95% CI: £181, £253]). Conclusions: In this analysis of HES data from England, about 14% of hospital spells coded with a primary diagnosis of HF included ID/IDA in the secondary position. These spells were longer, more expensive, and more likely to lead to readmission. Although probably under recognised in those admitted with HF, ID/IDA appears to be a significant comorbidity associated with poorer outcomes across the health economy.